ANALISIS KEYAKINAN HAKIM DIDALAM MENJATUHKAN SANKSI PIDANA TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA PENCURIAN (CONTOH KASUS PUTUSAN NO. 35/PID.SUS-ANAK/2020/PN LLG) - Tri Guntur Julianto; R Rahaditya (Jurnal Hukum Adigama, 2021)
The judge's confidence in handing down criminal penalties against the child as the perpetrator of criminal theft should best reflect justice and have benefits for all parties, both child and victim. The study aims to know how the judge's conviction in handing out criminal penalties against the child as perpetrators of a felony theft at rule number 35/ pid. Sus-child /2020/ pn has been consistent with the 2012 law number 11 on the child's criminal justice system and to find out if the judge is on ruling 35/ pid. Sus-Anak /2020/ pn.llg already passed criminal sanctions under the 2012 statute of 11 on the child criminal justice system. The type of research used in this study is normative-law research and USES primary law materials includes laws, secondary law materials of books, the study USES legislation approaches and case approaches related to the problems studied, the writer analyzes data by deductive methods. Judge's confidence in ruling 35/Pid. Sus-Anak/2020/pn.llg will be precise but in dropping criminal sanctions on children as criminal offenders is less appropriate because the judge in its sentence reflects justice restorative/ restorative justice justice and is based on principle in article 2 rule number 11 in 2012 about the child's criminal justice system. Therefore the judge should be in the casting of a criminal sentence against the child should reflect restorative justice and be based on the principle on the 2012 no. 11 year law on the child's penal system.